ÇEŞİTLİ KLİNİK ÖRNEKLERDEN İZOLE EDİLEN STAFİLOKOKLARA KARŞI MOKSİFLOKSASİN DUYARLILIĞININ ARAŞTIRILMASI - ŞENOL, FERAY FERDA (Fırat Üniveristesi, 2004)
Stafilokoklar hastane infeksiyonu etkenleri arasında ilk sıralarda yer alan mikroorganizmalardır. Dirençli suşlarm artarak yayılması nedeniyle, bu mikroorganizmalara bağlı infeksiyonların tedavisinde çeşitli zorluklar yaşanmaktadır. Özellikle metisiline dirençli stafilokoklar ile oluşan infeksiyonların tedavisinde kullanılabilecek antibiyotik sayısı sınırlıdır, moksifloksasin; son yıllarda kullanıma girmiş, kinolon grubundan, metisiline dirençli ve duyarlı stafilokoklann tedavisinde seçenek olan bir antibakteriyel ajandır. Bu çalışmada; moksifloksasinin yöremizde izole edilen stafilokok suşlan üzerindeki etkinliğini belirlemek amacıyla, çeşitli klinik örneklerden izole edilen metisiline dirençli ve duyarlı stafilokoklann moksifloksasin duyarlılıkları disk difîuzyon ve MIC yöntemiyle araştırıldı. Fırat Üniversitesi Tıp Fakültesi Mikrobiyoloji ve Klinik Mikrobiyoloji Anabilim Dalı Bakteriyoloji Laboratuarında; Fırat Tıp Merkezinin çeşitli kliniklerinden gönderilen kan, balgam, idrar ve yara kültür örneklerinden izole edilen 160 S. aureus ve 40 koagülaz negatif stafilokok (KNS) susu çalışmaya alındı. Disk diffiizyon yöntemi ile 160 S.aureus susundan 132'si (%82.5), 40 KNS susundan 33 'ü (%82.5) moksiffoksasine duyarlı bulundu. MIC yöntemi ile 160 S.aureus susundan 146'sı (%91.2), 40 KNS susundan 35'i (%87.5) moksiffoksasine duyarlı bulundu. Sonuç olarak kinolonlann gelişigüzel kullanımı, özellikle stafilokok infeksiyonlannda direnç problemini ortaya çıkarmıştır. Çalışmamızda, moksifloksasinin stafilokoklara karşı yüksek oranda etkinlik gösterdiği gözlenmiş olduğundan, klinikte geniş kullanım alam bulacaktır.Anahtar Kelimeler : Stafilokok, moksifloksasin, MIC, disk diffuzyon. 2. ABSTRACT Staphylococcus are the major microorganisms which can be regarded in the nosocomial infections. Staphylococcal infections are often associated with therapuetic diffucilty due to widespread distribution of these organisms. The numbers of appropriate antibiotics are severely limited in the infections particularly with methicillin-resistant staphylococcal strains. Moxifloxacin is a new quinolone derivative that has been recently submitted to clinical use, may be a good alternative agent in the infections by both methicillin-resistant and susceptible staphylococcal strains. In this study, we aimed to investigate in vitro moxifloxacin activity by using disc-diffusion and microdilution methods against to methicillin-resistant and methicillin-susceptible staphylococci which were isolated from several clinic samples, in our region. The study was took place in bacteriology laboratory of Medical Microbiology Department of Fırat University's Medical School. Total 160 Staphylococcus aureus and 40 coagulase negative staphylococci (CNS) were included. Staphylococcus were isolated from blood, sputum, urine and wound samples from different clinics in Fırat Medical Center. In disc-diffusion method; 132 (82.5%) of 160 Staphylococcus aureus and 33 (82.5%) of 40 coagulase negative staphylococcus were determined as susceptible for moxifloxacin. In microdilution method; 146 (91.2%) of 160 Staphylococcus aureus and 35 (87.5%) of 40 coagulase negative staphylococcus were determined as susceptible for moxifloxacin.

Anahtar Kelimeler : Stafilokok, moksifloksasin, MIC, disk diffuzyon. 2. ABSTRACT Staphylococcus are the major microorganisms which can be regarded in the nosocomial infections. Staphylococcal infections are often associated with therapuetic diffucilty due to widespread distribution of these organisms. The numbers of appropriate antibiotics are severely limited in the infections particularly with methicillin-resistant staphylococcal strains. Moxifloxacin is a new quinolone derivative that has been recently submitted to clinical use, may be a good alternative agent in the infections by both methicillin-resistant and susceptible staphylococcal strains. In this study, we aimed to investigate in vitro moxifloxacin activity by using disc-diffusion and microdilution methods against to methicillin-resistant and methicillin-susceptible staphylococci which were isolated from several clinic samples, in our region. The study was took place in bacteriology laboratory of Medical Microbiology Department of Fırat University's Medical School. Total 160 Staphylococcus aureus and 40 coagulase negative staphylococci (CNS) were included. Staphylococcus were isolated from blood, sputum, urine and wound samples from different clinics in Fırat Medical Center. In disc-diffusion method; 132 (82.5%) of 160 Staphylococcus aureus and 33 (82.5%) of 40 coagulase negative staphylococcus were determined as susceptible for moxifloxacin. In microdilution method; 146 (91.2%) of 160 Staphylococcus aureus and 35 (87.5%) of 40 coagulase negative staphylococcus were determined as susceptible for moxifloxacin.As a result, we concluded that excessive quinolone use has yielded to severe antimicrobial resistance in staphylococci. Due to high activity of moxifloxacin against staphylococcus, it will be a good alternative antibiotic in staphylococcal infections. Key Words : Staphylococcus, moxifloxacin, MIC, disc diflution.
Bu tezin, veri tabanı üzerinden yayınlanma izni bulunmamaktadır. Yayınlanma izni olmayan tezlerin basılı kopyalarına Üniversite kütüphaneniz aracılığıyla (TÜBESS üzerinden) erişebilirsiniz.
Keywords: Mikrobiyoloji; Microbiology